An integrated workflow to characterize and evaluate low resistivity pay and its phenomenon in a sandstone reservoir - Pratama, E. (Institute of Physics Publishing, 2017)
The identification, characterization and evaluation of low resistivity pay is very challenging and important for the development of oil and gas fields. Proper identification and characterization of these reservoirs is essential for recovering their reserves. There are many reasons for low resistivity pay zones. It is crucial to identify the origin of this phenomenon. This paper deals with the identification, characterization and evaluation of low resistivity hydrocarbon-bearing sand reservoirs in order to understand the low resistivity phenomenon in a sandstone reservoir, the characterization of the rock types and how to conduct petrophysical analysis to accurately obtain petrophysical properties. An integrated workflow based on petrographical, rock typing and petrophysical methods is conducted and applied. From the integrated analysis that was performed, the presence of illite and a mixed layer of illite-smectite clay minerals in sandstone formation and pyrite-siderite conductive minerals was identified as one of the main reasons for low resistivity occurence in sandstone reservoirs. These clay minerals are distributed as a laminated-dispersed shale distribution model in sandstone reservoirs. The dual water method is recommended to calculate water saturation in low resistivity hydrocarbon-bearing sand reservoirs as this method is more accurate and does not result in an over estimation in water saturation calculation. © 2017 Sinopec Geophysical Research Institute.